Fodor's 2009 Chicago. (New York : Fodors's Travel, 2009)
A comprehensive guide to visiting Chicago that provides information on neighborhoods, museums, shopping, restaurants, entertainment, activities, accommodation, and more; and offers detailed maps and trip planning advice.
Cover title: Chicago 2009.
Includes index.
Includes pull-out map.
Maps on inside covers.
Young Adult
Keywords: Chicago (Ill.) -- Guidebooks; Chicago (Ill.) -- Description and travel; Chicago (Ill.) -- Guidebooks; Chicago (Ill.) -- Description and travel